THE HIDDEN RISKS BEHIND ENERGY DRINKS: THREATS TO REPRODUCTIVE HEALTH AND THE NERVOUS SYSTEM - Izbasarov Islomjon Ilkham ogli; Namozov Islombek Rustam ogli; Toshmatova Guzal Adilkhodjayevna (Web of Journals Publishing, 2025)
This research investigates the potential harmful effects the energy drinks may have on human health, particularly concerning the reproductive and nervous systems. The sharp increase in energy drink consumption among youth populations has made understanding their biological impact mechanisms critically important from both scientific and public health perspectives. Through an online survey methodology, researchers examined consumption frequency, individual responses to caffeine and other stimulants contained in these products, and health changes experienced by participants. Results demonstrated that habitual energy drink intake correlates with adverse reproductive outcomes, including hormonal imbalances affecting sexual health, menstrual disturbances, and compromised sperm quality. Furthermore, participants reported heightened nervous system complications including sleep deprivation, persistent headaches, cardiac palpitations, and impaired cognitive focus. The study concludes that sustained energy drink consumption presents substantial threats to both reproductive wellness and neurological function, emphasizing the urgent need for comprehensive laboratory-based and clinical research in this area.
Keywords: Energy drinks, caffeine, taurine, stimulants, reproductive health, nervous system, hormonal imbalance, sperm quality, menstrual disturbances, sleep disorders.